Cancer Therapy: Targeting Mitochondria and other Sub-cellular Organelles - C. Ubah, Obinna; M. Wallace, Heather (Current Pharmaceutical Design, 2014)
Tumour cell death is required for the clearance of malignant cells and is a vital part of the mechanism of natural tumour suppression. Cancer cells, having acquired multiple deregulated pathways involving several cellular oragenelles, are capable of disrupting these normally finely tuned processes thereby evading both physiological and therapeutic intervention. Although current available data indicate the dependence of successful tumour cell clearance on classical apoptotic pathways (intrinsic and/or extrinsic pathways), there is now evidence suggesting that alternative apoptotic and non-apoptotic pathways may effectively contribute to tumour cell death. The mitochondria, proteasomes, endoplasmic reticulum, Golgi apparatus, lysosomes and lysosome-related organelles of tumour cells exhibit a number of deregulations which have been identified as potential druggable targets for successful rational drug design and therapy. In this review, we summarise the roles of these cellular organelles in tumour initiation and establishment as well as current trends in development of agents that target deregulations in these organelles.
Keywords: polyamines